ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONDISI FINANCIAL DISTRESS BANK PERKREDITAN RAKYAT - Effendi, Satrio Arga; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
This research aimed to analyze the factors affecting the financial distress of rural banks in West Sumatera. By using the technique of multiple linear regression analysis, and the latest prediction model of financial distress